Thermal studies on solid 1,4-bis(3-carboxy-3-oxo-prop-1-enyl) benzene of lighter trivalent lanthanides - Nunes, Ronaldo S. [UNESP]; Bannach, Gilbert [UNESP]; Luiz, Jose M. [UNESP]; Caires, Flavio J. [UNESP]; Carvalho, Claudio T.; Ionashiro, Massao [UNESP] (Springer, 2011)
Solid-state compounds of general formula Ln(2)L(3)center dot nH(2)O, where L represents 1,4-bis(3-carboxy-3-oxo-prop-1-enyl)benzene and Ln = La, Ce, Pr, Nd, Sm, were synthesized. Complexometric titrations with EDTA, thermogravimetry (TG), differential thermal analysis (DTA), differential scanning calorimetry (DSC), X-ray powder diffractometry, elemental analysis and infrared spectroscopy have been employed to characterize and to study the thermal behavior of these compounds in dynamic air atmosphere. The results led to information about the composition, dehydration, crystallinity, and thermal decomposition of the synthesized compounds.
Keywords: 1,4-bis(3-carboxy-3-oxo-prop-1-enyl) benzene; Lighter lanthanides; Thermal behavior